THE OPTIONAL PROTOCOL TO THE INTERNATIONAL COVENANT ON ECONOMIC, SOCIAL AND CULTURAL RIGHTS: A NEW INSTRUMENT TO ADDRESS HUMAN RIGHTS VIOLATIONS - Courtis, Christian (Espaço Jurídico Journal of Law [EJJL], 2015)
The article discusses the adoption of the new Optional Protocol to the International Covenant on Economic, Social and Cultural Rights as a means to obtain redress for violations against economic, social and cultural rights in the international sphere – including its potential use for the consideration of the violation of extraterritorial obligations. Keywords: Human rights. Social rights. Violations. Optinal protocol.